Branding of Wasuemba Tourism Village and Strengthening of Lahunduru Tourism Awareness Groups - Maulana, Harry Fajar; Sa'ban, L.M. Azhar; Ardiansah Putra, Muhammad Rizal; Sari Anwar, Nirmala (Room of Civil Society Development, 2025)
Community service activities were carried out in Wasuemba Village, Buton Regency with participants from the Lahunduru Tourism Awareness Group. Wasuemba Village has tourism potential that can be developed as a tourist village. Wasuemba village has many interesting and unique things that can be presented to visitors/tourists who come to this place. Some of the partner's priority problems, namely the Lahunduru Tourism Awareness Group of Wasuemba Village has not prepared a mature concept for branding activities and the unavailability of human resources in managing the branding of Wasuemba Tourism Village. The Lahunduru Tourism Awareness Group of Wasuemba Village is still lacking in branding Wasuemba Tourism Village, digital technology media is a means of marketing or digital marketing to advance the products they want to market. The data and information will make it easier for the Tourism Awareness Group to create or develop something that they want to market. The purpose of this service is to increase the knowledge and ability of the Lahunduru Tourism Awareness Group in branding Wasuemba Tourism Village so that it can target tourists. The method used in this community service activity is to conduct a survey, then conduct a needs analysis by the PKM Team, after that proceed with socializing and assisting PKM activities. The results of this activity were that the Lahunduru Tourism Awareness Group of Wasuemba Village received information about tourism awareness groups that are actors driving village tourism, and the Lahunduru Tourism Awareness Group received additional knowledge related to branding tourist villages.